Religious policy of Kazakhstan in the years of restriction (1985–1991) - Junusbayeva, А.М. (KU Publ., 2022)
The State’s religious policy was part of a policy of restructuring during the period under review. However, the early years of restructuring ideological inertia were still strong, and preserved inductions into the increasing atheistic educational work. Authorities considered ideological rival in the religion not an ally. It was due to the inadequate dissemination of democratic processes in the public life of the Republic. Another reason for the stability of the state policy towards religious organizations and believers, especially Muslims, was the foreign policy factor. The meeting between N. Nazarbaev and representatives of religions was an important event which had a great importance in implementing new approaches. Special emphasis was placed on the need for clergymen to do more to disseminate and observe universal human moral and ethical principles, mercy, charity, protection of motherhood and childhood, and help the disabled and the elderly people. There was adopted the Law of the USSR “On freedom of conscience and religious organizations”. The documentchanged the situation of religious organizations in the country, proclaiming democratic principles and norms. The new law reflected a new balanced and objective approach to religion and religious organizations. The rights of religious organizations have been considerably expanded and many unjustified restrictions have been removed from their activities in public life. The law enshrines respect for believers and religious organizations. The role of religion and religious organizations in society is being redefined and it grows the significance of confessions in the history and culture of the people. The religious policy of the state during the years of reconstruction served as a basis for the creation of a modern model of interfaith harmony in the country and contributed to the process of religious revival which is connected with the interest to religion as part of culture.
Қайта құру жылдардағы Қазақстанның діни саясаты (1985–1991 жж.)
Религиозная политика Казахстана в годы перестройки (1985–1991 гг.)
Keywords: restructuring; religion; state; politics; atheistic work; church; mosque; temple; inertia; law; relations